Teleodynamic Timber Façades - Larsson, Magnus; Wålinder, Magnus; Falk, Andreas (Frontiers in Built Environment, 2018)
This paper investigates ways in which weathering-related site conditions can be allowed to inform the design process in order to improve a building’s geometry and performance. Providing a building design with the capacity to remember past experiences and anticipate future events can provide substantial gains to the architectural configuration and engineering of a timber façade. A new theory of architecture is outlined based on recent “teleodynamic” theories – a hypothesis about the way far-from-equilibrium systems interact and combine to produce emergent patterns. The proposed explanation considers nested levels of thermodynamic systems applied to an architectural context: “homeodynamic” operations that involve equilibration and dissipation of constraint combine to produce self-organising “morphodynamic” procedures that amplify and regularise site-specific constraining data streams. A teleodynamic design reconstitutes itself by combining morphodynamic processes so as to optimise its relationship to the past, present, and future. A novel teleodynamic design tool called Contextual Optimisation Workspace (COW) is assembled within the Grasshopper visual programming environment. The tool is used to carry out four experiments that combine to produce the teleodynamic design of an urban wooden façade, exemplifying an alternative framework for the design of wood-based structures. The first experiment investigates a variegated grid combining two distinct subdivision methods (an orthogonal grid and a Voronoi tessellation), transmuting one system into another. The second and third experiments focus on durability aspects of a wooden façade and devise strategies for how the effects of photochemical degradation and wetting due to driving rain might be minimised using the COW tool. The fourth experiment optimises the building for daylight based on an illuminance simulation. Using simulation and anticipation to add the advantages of site- and time-specific data streams as a design strategy can effectively suspend an algorithm-driven design iteration in time and space in order to allow it to be parametrically influenced by past or future events such as unique site and project conditions. The COW tool can be used to produce such teleodynamic designs.